“Not what it seems to be” : A rare case of left ulna brodie’s abscess in children - Elsonmond Vick, Duin; Chan, Wai Hoong; Mohammad Zaki, Haji Mohd Amin (2021)
Introduction: Brodie abscess is a subacute hematogenous osteomyelitis characterized by intraosseous abscess formation. It is typically localized in the metaphysis of tubular bones, particularly in the lower limbs. The diagnosis in upper extremities is challenging and can mimics bone tumor because there is no characteristic finding on an X-ray and no obvious inflammatory response. There's very few study reporting Brodie Abscess in upper extremities especially Ulna Bone. The treatment is drainage and curettage that leaves large cavity requiring bone grafting. This a case of Brodie's abscess in the left ulna healed with spontaneous rupture and antibiotic. Discussion: A 7 year-old girl presented with a month history of left distal forearm painless swelling. There was no history of trauma, constitutional symptom or febrile illness prior to presentation. At first presentation, the examination revealed a well defined swelling 4x3 cm, firm to hard consistency, fixed to the underlying structures but not to the overlying skin. The plain X-ray of left radius ulna showed radiolucent expansile lytic lesion of the diaphysis of ulna bone with nidus formation with distal ulna cortical destruction. Blood tests showed normal white count and inflammatory markers. While waiting for scheduled MRI, she had a painless sinus discharging pus of the left distal forearm and a reduction in the size of the swelling. She was otherwise well. The second left ulna plain radio-graph shows less lucency with improved distal ulnar cortex appearance. Diagnosis of brodie's abscess is obtained following radiographic nidus formation with self-drained abscess. She was treated with cefuroxime for eight weeks. Conclusion: Brodie's abscess of the ulna is rare and never been reported before in the literature. The Xray may mimic bone tumor presentations. MRI and tissue biopsy is required to confirm diagnosis. In our case, she had a spontaneous ruptured swelling while waiting for MRI and treated non operatively.